Community Repertoires in Chile: Between Neoliberal Institutional Frameworks and Relative Autonomy (Andamios, Revista de Investigación Social, 2025)
In Chile, the neo-liberal model has consolidated a political-cultural framework that favors depoliticized, fragmented, and bureaucratized community life. Nevertheless, community praxis emerges across a broad spectrum of community repertoires. This article, based on focus groups conducted in Talca, Chile, examines these repertoires and their expression in different forms of politics, autonomy and articulation of what we term the community sphere. The text is organized into four sections: a conceptual framework on forms of community production; a description of the methodological process; a presentation of the results across four areas of analysis (meaning of the organization, organizational forms, articulation practices, and relationship with the State); and conclusions and reflections derived from these findings. A central finding is that community organizations face a duality: while conditioned by the dominant institutional framework, they deploy their own forms of community production that transition between adaptation, debate, and transformation. Additionally, the study emphasizes that these repertoires are not separate compartments, but rather complementary dimensions that organizations combine and redefine according to their contexts, resources, and trajectories. This richness and diversity constitute a potential basis for strengthening collective life and challenging meanings in an adverse environment.
Keywords: Organizations; community sphere; autonomy; production of the community; Chile